Determinan Faktor Pengungkapan Modal Intelektual dan Tingkat Pengungkapan Per Industrinya pada Seluruh Perusahaan yang Terdaftar di Bursa Efek Indonesia - Rezki, Sri Budhi (Kompartemen : Jurnal Ilmiah Akuntansi, 2018)
This study aims to examine the influence of corporate governance mechanisms and company characteristics towards the extent of intellectual capital disclosure. The independent variable in this research is proportion ofÂ independence board, size of audit committee, profitability, age of company,Â size of company, and type of industries. The dependent variable in this research is intellectual capital disclosure level. The sample used in this research was annual reports all of company listed at Indonesia Stock Exchange. The sampling technique used in this study is purposive sampling. With this method, the samples were 146 firms. The analysis of this study uses multiple linear regression. The results of this study indicated that size of audit committee, profitability, size of company, and type of industries had positive and significant influence on extent of intellectual capital disclosure. Eventhough, proportion of independence board and age of company had no significant.